Descriptive and Comparative Analysis of Labor IQ in Indonesia by Gender, Age, Education, and Provincial Domicile - Wikantiyoso, Bimo; Budisetyono, Gracia Amanda Sam; Setiawan, Alvin Benedict (Journal of The Community Development in Asia, 2024)
The study aimed to analyze variations in intelligence (IQ) across demographic factors, including gender, age, education, and geographical location, to explore their influence on IQ scores. Utilizing a cross-sectional quantitative research design and convenience sampling, data were analyzed using descriptive and cross-tabulation methods. The results showed no significant difference in IQ scores between males and females, challenging the initial hypothesis regarding gender differences. Additionally, no significant differences were found between age groups, contradicting the expectation that age would influence IQ, specifically through fluid and crystallized intelligence. In contrast, educational level showed a significant positive correlation with IQ scores, confirming the role of education in shaping intelligence. Geographical origin, particularly environmental factors such as access to education and nutrition, did not significantly affect IQ scores, likely due to the homogeneous socioeconomic conditions among the predominantly Java-based sample. These findings highlight the complexity of intelligence determinants and question prior assumptions about demographic influences on IQ.